Penerapan Strategi Digital Marketing Pada Usaha Mikro, Kecil, Menengah (UMKM) Fire Chicken Purwokerto - Andara Kesya Saputra; Naira Hasifa (Jurnal Ilmiah Raflesia Akuntansi, 2026)
Abstrak— The purpose of this study is to ascertain how Fire Chicken UMKM implements digital technology and marketing.UMKM are crucial to the Indonesian economy, especially when it comes to generating jobs and promoting regional and national economic expansion. Using information and communication technology to assist business activities is oneway UMKM may stay competitive in the age of digitalisation and continue to expand. Business players must adopt digital marketing tactics in order to broaden their market reach and boost sales, as the evolution of internet technology has caused a shift in marketing trends from traditional to digital. This study employs a descriptive, qualitative methodology. The manager of Fire Chicken UMKM, who is thought to be knowledgeable with the digital marketing tactics used by the company, is the research informant for the purposive sampling technique. About 70% of total sales come from digital marketing, with online channels and the DO system accounting for 60% of revenues Keywords: Digital Marketing, UMKM, Social Media, Digital Technology, Marketing